hallenges Faced by EFL Teachers and Students On Writing Skills Case study of Third Year English language Students At Souk-Ahras University - CHENCHE Rayene (My University, 2022)
Abstract The present study aims to investigate the writing challenges that encounter EFL teachers and students in the Department of English at Mohammed-Cherif Messaadia University, in Souk-Ahras. The writing challenges are manifested in a linguistic form like spelling, grammar, vocabulary, punctuation… which make the writing process heavy for the students to assimilate; together they give sense to the psychological challenges that involve students’ anxiety, de-motivation and the negative attitude they carry towards written tasks, adding to this some other pedagogical challenges that is related to the teacher and the teaching context. To test the suggested hypothesis, a questionnaire for both EFL teachers and students is used. The results revealed that most of EFL students face common challenges in writing skills; though overcoming them will help students to boost their writing competence. Teachers on the other hand, agreed that students’ lack of motivation and neglecting the techniques and strategies of writing would not help them in teaching. Eventually, the analysis of the data collected from the employed research instruments allows in confirming the raised hypothesis, and in light of the findings there is a need to put forward a number of pedagogical recommendations aiming at enhancing teaching and learning the  writing skill among third-year English students.